Nonspecific cervical spine pain/neck pain/in medical personnel of north-eastern Poland—A cross-sectional study - Citko, Anna; Górski, Stanisław; Marcinowicz, Ludmiła; Mateusz, Cybulski; Matylda, Sierakowska (Frontiers in Medicine, 2024)
Both mechanical and psychological overload are inherent to the work of nurses and paramedics, resulting spondylogenic pain. Aim of the study To identify potential risk factors influencing the prevalence of non-specific cervical spine pain in professionally active nurses and paramedics. Material and methods 324 nurses (53.2% of the total) and 285 paramedics (46.8%) were included in the study−609 people in total. The study was carried out using an auditorium survey technique supervised by the researchers. The methods used were: Nordic Musculoskeletal Questionnaire, a spinal pain questionnaire validated according to IEA guidelines, a short version of the IPAQ and the author's survey questionnaire, concerning sociodemographic data, chronic diseases including metabolic syndrome (MetS). A univariate logistic regression model was used in the statistical analysis. The level of statistical significance was taken as p < 0.05. Results Recurrent NP was significantly more common in paramedics compared to nurses (29.5 % vs. 9.3 %; p < 0.0001). In a univariate logistic regression model, the risk of NP was significantly increased by: length of service > 15 years (p < 0.024), presence of: low back pain (p < 0.0001), type 2 diabetes (p = 0.013), hypertension (p < 0.001), depression (p < 0.01). Of the modifiable factors, the risk of NP was significantly increased by high physical activity and short sleep <7 h (p < 0.001).